2016
DOI: 10.1093/ptep/ptw150
|View full text |Cite
|
Sign up to set email alerts
|

Effective potential from zero-momentum potential

Abstract: We obtain the centre-of-mass frame effective potential from the zeromomentum potential in Ruijsenaars-Schneider type 1-dimensional relativistic mechanics using classical inverse scattering methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The Ruijsenaars-Schneider (RS) model [12,13] is an integrable relativistic quantum mechanical model whose dynamics and S-matrix is completely equivalent to that of the SG field theory. From the RS description it is possible to read off the corresponding zero-momentum potential [13,11]. In our conventions it reads (after restoring the constants , c)…”
Section: B the Sine-gordon S-matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ruijsenaars-Schneider (RS) model [12,13] is an integrable relativistic quantum mechanical model whose dynamics and S-matrix is completely equivalent to that of the SG field theory. From the RS description it is possible to read off the corresponding zero-momentum potential [13,11]. In our conventions it reads (after restoring the constants , c)…”
Section: B the Sine-gordon S-matrixmentioning
confidence: 99%
“…The Ising model and the O(3) nonlinear σ-model were studied and it was found that at low energies the energy-dependent U E (x) can be well approximated by its zero-momentum limit (corresponding to the case where the relative momentum of the two-particle state vanishes). The problem was also studied in the Sine-Gordon (SG) model [11]. In the semiclassical limit an energy-independent effective potential was constructed, which exactly reproduces the semiclassical time delays for all energies.…”
Section: Introductionmentioning
confidence: 99%